From ballot-boxes to barracks: Votes, institutions, and post-election coups. (March 2019) - Rozenas, Arturas; Zeigler, Sean M
The military often intervenes in politics shortly after elections. This might be because election results reveal information about the ease with which a coup can succeed. Would-be coup perpetrators use this information to infer whether the incumbent can be removed from office without provoking popular unrest. We argue that the informational content of elections depends on the electoral rules that translate votes into outcomes. In electoral systems that incentivize strategic voting, election returns are less informative about the distribution of political support than in electoral systems that incentivize sincere voting. An extensive battery of statistical tests shows that vote-shares of election winners do not predict coup attempts in plurality systems, which encourage strategic voting, but they do predict coup attempts in non-plurality electoral systems, which do not encourage strategic voting. Thus, incumbents who have performed well in elections face a lower risk of coup attempts, but only in institutional environments where voting results are highly informative about the distribution of political support. We apply this logic to illuminate the decisions of the military to intervene into politics during the famous failed 1936 coup in Spain and the successful 1973 coup in Chile.